Comparison between pharmacological and surgical approaches in the treatment of obesity (International Seven Journal of Multidisciplinary, 2024)
Introduction: Obesity is a growing global health condition, with serious implications for the health and quality of life of affected individuals. Approaches to the treatment of obesity include pharmacological and surgical interventions, each with its specific efficacy and safety profile. Objective: The objective of this study is to compare the efficacy, benefits, harms and prognosis of pharmacological and surgical approaches for the treatment of obesity, based on recent data from the scientific literature. Methodology: An integrative literature review was conducted using the PubMed and ScienceDirect databases. The search was conducted with the search key ("obesity" OR "overweight") AND ("anti-obesity drugs" OR "pharmacotherapy" OR "antiobesogenic agents") AND ("bariatric surgery" OR "weight loss surgery" OR "surgical treatment"). Studies published between 2019 and 2024 were selected, including clinical trials, meta-analyses, and systematic reviews. Results and Discussion: The review found that pharmacological approaches, such as semaglutide and liraglutide, are effective in weight loss and control of associated comorbidities, but require ongoing adherence to treatment and may cause side effects. Bariatric surgeries, such as gastric bypass and sleeve gastrectomy, offer substantial weight loss and significant improvement in comorbidities, but with a higher risk of complications and the need for reinterventions. Conclusion: Both approaches have merits and limitations. The choice between pharmacological and surgical treatment should be based on the individual characteristics of the patients and the specific treatment needs. Bariatric surgery has better results in terms of long-term weight loss and resolution of comorbidities, while medications offer a less invasive alternative.